1991
DOI: 10.1002/lary.5541011211
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic changes in snoring and obstructive sleep apnea syndrome

Abstract: The pathophysiologic events that lead to the loss of airway compensation in obstructive sleep apnea (OSA) are poorly understood. The development of airway instability may be secondary to changes in neurologic control, airway morphology, or both. To identify potential histopathologic features of pharyngeal tissues that may contribute to OSA, transverse sections of the distal soft palate and uvula were qualitatively compared using light and electron microscopy from 4 severe apneics (>50 apnea/hour), 4 severe sno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
123
2
11

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(147 citation statements)
references
References 9 publications
11
123
2
11
Order By: Relevance
“…14,15 On the other hand, morphological abnormalities of the palatopharyngeus muscle have been found by Friberg et al 16 in SAHS compared to snorers and normal non-snorers, with an increased proportion of atrophic and hypertrophic ®bers, an increased number of angulated atrophic ®bers, and a high number of muscle ®bers exhibiting similar myosin ATPase characteristics and located within a narrow region (a phenotype commonly described as ®ber type grouping). These results are consistent with those of Woodson et al, 17 who found frequent focal degeneration of myelinated nerve ®bers in SAHS.…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…14,15 On the other hand, morphological abnormalities of the palatopharyngeus muscle have been found by Friberg et al 16 in SAHS compared to snorers and normal non-snorers, with an increased proportion of atrophic and hypertrophic ®bers, an increased number of angulated atrophic ®bers, and a high number of muscle ®bers exhibiting similar myosin ATPase characteristics and located within a narrow region (a phenotype commonly described as ®ber type grouping). These results are consistent with those of Woodson et al, 17 who found frequent focal degeneration of myelinated nerve ®bers in SAHS.…”
Section: Introductionsupporting
confidence: 93%
“…18 However, only a small number of the patients included in the two above-mentioned studies 16,17 had conventional sleep evaluation to document and con®rm their abnormal nocturnal breathing status, as in the Friberg study patients were classi®ed according to unconventional scoring of nocturnal breathing abnormalities (percentage of periodic obstructive breathing using a sleep apnea mattress). Furthermore, Woodson et al did not compare muscle characteristics of SAHS with those of non-apneic snorers, Therefore, the respective effects of UA trauma consecutive to UA collapse and the consequences of snoring and UA¯uttering en morphological characteristics of UA muscle remained to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…These changes surprisingly affected all dogs in brachycephalic group classified as Grade I BAOS patients. Similar microscopical findings characterize the soft palate in human patients with obstructive sleep apnea syndrome (OSAS) (Woodson et al, 1991;Hamans et al, 2000;Berger et al, 2002).…”
Section: Discussionmentioning
confidence: 65%
“…Since palatine gland hyperplasia was present in all the brachycephalic dogs considered in this study, diet factors are less likely responsible for this feature. Vibrations and friction of soft palate during inspiratory efforts and snoring could represent valid causes for palatine gland hyperplasia to occur as defensive mechanism (Woodson et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…There is morphologic evidence to support the presence of a sensory neuropathy in the UA in obstructive sleepdisordered breathing [16][17][18] .…”
Section: Discussionmentioning
confidence: 99%